(3N+1)-frame phase retrieval for double-grating Ronchi lateral shearing interferometry. (November 2022) - Lu, Yunjun; Tang, Feng; Su, Rong; Li, Zhongliang; Guo, Fudong; Feng, Peng; Wang, Xiangzhao
Highlights: A new shear-phase retrieval algorithm for double-grating Ronchi lateral shearing interferometry is proposed. The algorithm allows for adjustable shear ratios without any hardware change. The algorithm can reject unwanted diffraction orders, verified by the spectral analysis using its frequency transfer function. Significant improvement on the accuracy of wavefront measurement is demonstrated in both experiment and numerical simulation. Abstract: Accurate wavefront measurement using double-grating Ronchi lateral shearing interferometry significantly relies on the accuracy of shear-phase retrieval. Traditional methods cannot effectively suppress the interferences of unwanted diffractions generated by the Ronchi grating at the image plane. In this paper, we propose a method that uses 3 N +1 shear interferograms to retrieve the shear phase, where N is a positive integer. The selection of N depends on the number of the diffraction orders existing in the shearogram. According to the numerical aperture of the optical system under test and the period of image grating, the interferograms corresponding to the specific 3 N +1 phase shifts are obtained, from which the shear phase is calculated. For validation, the frequency response of the proposed algorithm is characterized, and the improved accuracy of wavefront measurement is demonstrated by comparisons with the existing 8-frame, 10-frame and 13-frame methods.